Blue Ocean Swimming Pool Service Center / Mohd Nasri A. Manan ... [et al.] - A. Manan, Mohd Nasri; Aii, Wan Syahrizal; Musa@Othman, Masjuraimi; Zakaria, Zafri; Abdul Samad, Rohaizat (Faculty of Sports Science and Recreation, 2006)
The business that establish is shareholder that depend on the shareholder act 1961. The business had been registered on the name of Blue Ocean Swimming Pool Service Center that address at No, 46G, Jalan. 27/70A Desa Sri Hartamas, 50480 Kuala Lumpur Business start operation on the 1st January 2002 that will focus on service of cleaning and maintenance swimming pool. This business is among four shareholder members that sponsor between RM 20,000 to RM14,000 each. We also had made a loan from Perwira Affin Bank to add our capitol. The total of loan that we made was RM 100,000,